UANG BUKAN SATU – SATUNYA ALAT TRANSAKSI EKONOMI (STUDI KASUS PADA PETANI DESA TAMBAKSARI KECAMATAN RUBARU) - Mohammad Rofik; Miftahol Arifin; Edy Purwanto; M. Munir Syam AR (Journal MISSY (Management and Business Strategy), 2022)
This research was conducted to find out that money is not the only tool used as a transaction in tambaksari village, Rubaru district. This type of research uses qualitative research with data analysis techniques for data reduction, data presentation and drawing conclusions. The results showed that the work system in agriculture in tambaksari village prioritizes family and mutual assistance, so that this causes the turnover of money to slow down and decreases the purchasing power of the people of tambaksari village.